Financial Performance of Jakarta Hospitals Before and After the COVID-19 Pandemic: Analysis of Profitability, Liquidity, and Leverage Ratios - Rorimpandey, Joel; Siagian, Harlyn; Malau, Harman (Ilomata International Journal of Tax and Accounting, 2025)
The COVID-19 pandemic has had a significant impact on the healthcare sector, particularly on hospitals, which faced operational and financial challenges due to increased operational costs and changes in service patterns. This study aims to evaluate the financial performance of hospitals in Jakarta before, during, and after the COVID-19 pandemic. The analysis was conducted using financial ratios, including Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM) to measure profitability; Current Ratio and Quick Ratio to measure liquidity; and Debt to Asset Ratio (DAR) and Debt to Equity Ratio (DER) to measure leverage. This study employed a quantitative descriptive method using secondary data in the form of financial statements from hospitals in Jakarta for the period 2018–2024. The results showed that profitability, liquidity, and leverage ratios experienced significant improvements during the pandemic compared to the pre-pandemic period. The Indonesian government's policy of funding COVID-19 patients played a major role in enhancing hospital financial performance during the pandemic. Furthermore, the financial performance of hospitals in Jakarta demonstrated a significant improvement post-pandemic compared to the pre-pandemic period. These findings provide valuable insights for hospital management and policymakers in formulating financial strategies to enhance the sustainability of hospital operations in the post-pandemic era.